Registration of title indispensable for peasant proprietors - Hutton, Henry Dix (Statistical and Social Inquiry Society of Ireland, 1882)
The subject of this paper is a branch of the large and difficult problem which increasingly engages the attention of social and legal reformers; how, namely, to combine security of titles to landed properties with facilities for dealings with them. It is a branch, however, which in Ireland, and at the present juncture, possesses extreme and exceptional importance, a satisfactory and prompt solution being urgently needed.
Papers read by members of the society at the social science congress, Dublin, October 1881
Keywords: Irish land question; Land reform; Peasant proprietors; Land registration; 314.15